Brain Slices From Human Resected Tissues - Heinemann, Uwe; Gabriel, Siegrun; Angamo, Eskedar A.; Salar, Seda; Lehmann, Thomas-Nicolas; Dengler, Nora (Models of Seizures and Epilepsy: Second Edition, 2017)
Human brain slices permit not only functional characterization of neuronal and nonneuronal cells in the hippocampus and cortex of patients surgically treated for tumors or pharmacoresistant epilepsy, including developmental disorders. They allow for detection of spontaneous activities, related to in vivo recorded EEG potentials, and also testing of hypotheses regarding increased seizure susceptibility. Underlying mechanisms can be investigated by inducing abnormal "epileptiform" activity. The properties of induced epileptiform activity might be evaluated in relation to pharmacoresistance and pathological diagnosis of the patient. Comparison of new pharmacological agents to standard AEDs might be helpful for new therapies. In some cases, alternative therapies, such as local delivery of drugs or deep brain stimulation protocols, can be proven. Importantly, organotypic slice cultures are maintained in vitro for prolonged periods, permitting toxicological studies and evaluation of slowly acting drugs.
Created from Fastlane, Scopus look-up
Keywords: Dentate gyrus; Extracellular recordings; Intracellular recordings; Intrinsic optical signals; Measurements of changes in ion concentration; New AEDs; Pharmacoresistance; Seizure like events; Subiculum; Temporal neocortex